2020
DOI: 10.1039/d0nr01005g
|View full text |Cite
|
Sign up to set email alerts
|

Permanent photodoping of plasmonic gallium-ZnO nanocrystals

Abstract: The concentration of delocalized electrons in plasmonic metal oxide nanocrystals can be increased permanently by photodoping because the electron compensation becoming the dominant compensation mechanism for the aliovalent donor dopant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The concept is inspired from photodoping of ultrasmall (quantum dot size) TiO 2 nanoparticles in hole scavenging media, where photogenerated holes are scavenged via photochemical oxidation of the alcohol while electrons populate the conduction band. , This, in turn, alter the electrical and optical properties of the TiO 2 nanoparticles. In the present case, we use the photodoping concept for detecting ethanol at room temperature in the presence of humidity.…”
Section: Introductionmentioning
confidence: 99%
“…The concept is inspired from photodoping of ultrasmall (quantum dot size) TiO 2 nanoparticles in hole scavenging media, where photogenerated holes are scavenged via photochemical oxidation of the alcohol while electrons populate the conduction band. , This, in turn, alter the electrical and optical properties of the TiO 2 nanoparticles. In the present case, we use the photodoping concept for detecting ethanol at room temperature in the presence of humidity.…”
Section: Introductionmentioning
confidence: 99%
“…31 Moreover, it has been demonstrated that permanent electron accumulation can be observed for ZnO nanoparticles when photodoped. 36 The electrons from photodoping remained stable in ZnO even after drying and keeping in the air for more than a month. The most responsive Ta-doped TiO 2 sample film was further studied in more detail.…”
Section: Resultsmentioning
confidence: 98%
“…Because localized electrons have less affinity toward participating in oxidation reactions, the defects in doped TiO 2 nanoparticles become relatively stable . Moreover, it has been demonstrated that permanent electron accumulation can be observed for ZnO nanoparticles when photodoped . The electrons from photodoping remained stable in ZnO even after drying and keeping in the air for more than a month.…”
Section: Resultsmentioning
confidence: 99%